Terminologia filozoficzna w nauce Ojców Kościoła - Leonkiewicz, Łukasz (Elpis, 2014)
Pre-Christian philosophy has formed land for the development of Christian theology, but first of all it has worked out notions enablingto describe the learning announced in the Bible. Vocabulary of notions handed over by the antiquity, new Christian, showed itself the age for Christian thinkers with foundation, on which the building of theology was made. Philosophical concepts such as ousia, hypostasis whether energyshowed themselves most suitable for describing the Christian dogma,but also with a view to describing the sphere of experience, spheres ofaction, philosophical terms were the most adequate. Philosophy playedthe major part in the process of developing of Christian theology, even if itself it didn’t create the last one. Full rejecting of the ancient conceptby Christian theologians wasn’t possible. Starting from St. Basil theGreat among theologians ruled a view that Christianity didn’t adopt from antiquity anything apart from notions. But many notions failed inthe philosophical thinking of the antiquity and even though they haveother meanings now, they can have them only because they developed,they lived their own life, in every age they were differently interpreted.The separation of philosophy and theology has never taken place fully,because it couldn’t have. Otherwise we would form something what in itform would resemble the attempt of interpretation of the New Testamentwithout taking Old into account.